The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-71672008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento, atitude e prática do uso de pílula e preservativo entre adolescentes universitários

Abstract: It was evaluated knowledge, attitude and practice concerning contraceptive pills and preservatives among teenagers at a public University of São Paulo. A Questionnaire was applied for 295 students. We verified that teenagers presented a positive attitude as to contraceptive practices because 92.6% of them said that adolescents should use contraceptive methods, and among those who had already initiated their sexual activities, 82% answered that they always used some type of contraceptive during their sexual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 10 publications
(19 reference statements)
0
19
0
13
Order By: Relevance
“…We must also consider the implications and impact of such early sexual initiation, often aggravated by lack of knowledge, reflection, and critical awareness of their behavior related to sex. As a consequence of these factors, unexpected pregnancy has been reported as a vulnerability in this phase of life (3,9,11) , and it may contribute to maternal and neonatal morbidity and mortality, along with birth complications, prematurity, and increased risk of miscarriage (12,13) . Another consequence of adolescent pregnancy is the dropout rate, which can reduce the opportunities for professional growth and development (6) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We must also consider the implications and impact of such early sexual initiation, often aggravated by lack of knowledge, reflection, and critical awareness of their behavior related to sex. As a consequence of these factors, unexpected pregnancy has been reported as a vulnerability in this phase of life (3,9,11) , and it may contribute to maternal and neonatal morbidity and mortality, along with birth complications, prematurity, and increased risk of miscarriage (12,13) . Another consequence of adolescent pregnancy is the dropout rate, which can reduce the opportunities for professional growth and development (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents' lack of concern may be related to the fact that their relationships are occasional (8) , as well as to early sexual initiation, because the earlier it happens the lower the chances of using contraceptive methods and, consequently, the higher the chances of pregnancy (19) . Regarding the responsibility of using a contraceptive method, a study conducted with adolescents at a public university in the state of São Paulo also reported that adolescents believe that the couple is responsible for it (3) . In this sense, counseling and prevention measures are essential not only for girls but also for boys in order to get them involved in the responsibility related to contraception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that adolescents of lower age and lower education become sexually active earlier, having less knowledge about MACs, while the older age, higher education and high family income have more knowledge. [5][6][7] Most contraceptive methods can be used by teenagers; however, the methods chosen and greater knowledge on these young people are constantly condom and oral and injectable contraceptives. 7 Although Family Planning program also should address the adolescent, guaranteeing him access to information of good quality and the availability of contraceptive alternatives, promoting his approach to the health service; not always the teenager believes his expectations met, which ends for distancing him from service units.…”
mentioning
confidence: 99%